2013
DOI: 10.1016/j.renene.2013.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Policy options for reducing the costs of reaching the European renewables target

Abstract: European governments have agreed to increase the share of renewable energy in final energy consumption to 20% by 2020. A crucial question for policy makers is how to mobilise the additional capital investments in RE and which consumer expenditures are involved. The article describes policy options for reducing renewable energy technology (RET) project costs as well as consumer costs, based on research conducted in de Jager et al., 2011 and Rathmann et al., 2011. The results show that risk-sensitive RET policie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 9 publications
0
36
0
1
Order By: Relevance
“…Haas et al, 2011;Klessmann et al, 2013;Mendonca, 2009) compared to U.S. policies consisting of a combination of tax credits, local incentives, and net-metering policies.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Haas et al, 2011;Klessmann et al, 2013;Mendonca, 2009) compared to U.S. policies consisting of a combination of tax credits, local incentives, and net-metering policies.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…It regards partial equilibrium energy system models, energy models dedicated to specific sectors, general equilibrium models, and macro-econometric models. In particular, the GREEN-X model underlines the development of RESs policy choices in energy sector [25] evaluating the possible impacts of green technologies costs on European 2020 targets [26].…”
Section: The Description Of the Modelmentioning
confidence: 99%
“…Several studies have shown that investment risks increase when switching from fixed feed-in tariffs to premium schemes, tenders or quotas (Rathmann et al 2011;Klessmann et al 2013;see, e.g., Kitzing 2014). For instance, while under feed-in tariff systems there is no risk in terms of price fluctuations, RES-E generators face price volatility under a quota system.…”
Section: Capital Market Failures and Other Obstacles To Long-term Rismentioning
confidence: 99%